Coronary sinus and atrioventricular groove avulsion after motor vehicle crash - Bradley M Dennis; Leigh Anne Dageforde; Rashid M Ahmad; Matthew J Eckert (Journal of Emergencies, Trauma and Shock, 2014)
Simultaneous cardiac and pericardial rupture from blunt chest trauma is a highly lethal combination with rarely reported survival. We report of a case of young patient with a right atrioventricular groove injury, pericardial rupture and a unique description of a coronary sinus avulsion following blunt chest trauma. Rapid recognition of this injury is crucial to patient survival, but traditional diagnostic adjuncts such as ultrasound, echocardiography and computed tomography are often unhelpful. Successful repair of these injuries requires high suspicion of injury, early cardiac surgery involvement of and possible even placement of the patient on cardiopulmonary bypass.